2005
DOI: 10.1002/pssc.200460240
|View full text |Cite
|
Sign up to set email alerts
|

host‐defect luminescence of stishovite

Abstract: A detailed study of the 4.75 eV luminescence band of stishovite single crystal (SiO 2 with rutile structure) is reported. Kinetics of luminescence intensity is studied at durable (tens of minutes) X-ray excitation. The observed behaviour of the band intensity is explained by creation and destruction of luminescence centres depending on temperature both being determined by radiation stimulated diffusion of atomic particles. The luminescence decay is observed to last for minutes after X-ray irradiation while onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…As previously stated [1,[3][4][5]7], we connect the luminescence of a single crystal of stishovite with similar luminescence (also two bands, blue and UV) in as-received oxygen deficient silica glass [13][14][15][16][17] and an analogous luminescence center in α-quartz crystal induced [9][10][11][12] with damaging radiation (γ, neutron and dense electron beam). That means similar defects are observed in these materials.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…As previously stated [1,[3][4][5]7], we connect the luminescence of a single crystal of stishovite with similar luminescence (also two bands, blue and UV) in as-received oxygen deficient silica glass [13][14][15][16][17] and an analogous luminescence center in α-quartz crystal induced [9][10][11][12] with damaging radiation (γ, neutron and dense electron beam). That means similar defects are observed in these materials.…”
Section: Discussionmentioning
confidence: 80%
“…It was also found that luminescence of stishovite single crystal appears both in recombination and intra center processes [1,[3][4][5], and in ionizing or photo irradiation. Additionally, in the case of poly-crystals, the photoluminescence excitation spectrum was measured [2].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In stishovite samples available for our investigation (synthetic monocrystals and Meteor Crater Arizona "natural" polycrystalline powder), there are two main luminescence bands: a blue one at about 3 eV and UV one at about 4.75 eV [1,[3][4][5]. In addition, a quasimolecular luminescence center ascribed to the presence of carbon impurity was found [7].…”
Section: Introductionmentioning
confidence: 84%